ZrO2 nanoparticles labeled via a native protein corona: detection by fluorescence microscopy and Raman microspectroscopy in rat lungs1. Issue 15 (7th August 2015) - Silge, Anja; Bräutigam, Katharina; Bocklitz, Thomas; Rösch, Petra; Vennemann, Antje; Schmitz, Inge; Popp, Jürgen; Wiemann, Martin
<x xml:space="preserve">Abstract</x> Raman microspectroscopy was applied to confirm the stability of a protein-based adsorptive labeling of ZrO2 NP inside the rat lung up to 3 d post application.